A Scoping Review of Biobehavioural Interventions to Improve PrEP Continuum of Care in Latin America - Vanessa Sánchez-Mendoza; Encarnación Soriano-Ayala; Pablo Vallejo-Medina; Omar Martínez (Acta Colombiana de Psicología, 2023)
According to the literature, biobehavioural interventions or combined strategies would reduce the risk of HIV infection by more than 7,000 new cases each day, which would contribute to the battle facing Latin America, where despite the high incidence and prevalence of HIV in the region, access to PrEP (pre-exposure prophylaxis) is very limited. The objective of this research was, consistent with the PRISMA guidelines (Preferred Reporting Items for Systematic Reviews and Meta-Analyses), to conduct a scoping review to assess the evidence of available outcome data on biobehavioural interventions and programs to address gaps in the PrEP continuum of care in Latin America. The search was conducted in the databases EBSCOhost, WoS, Scopus, and ProQuest, and include all studies published from 2010 to 2021. One hundred eighty-six studies were identified and evaluated according to the eligibility criteria in six stages starting with the elimination of du-plicates until the selection of studies that met the previously mentioned criteria; at the end five studies were chosen which were submitted to the methodological quality assessment including compliance with ethical guidelines. Results show that biobehavioural interventions promoting PrEP in Latin America are effective in increasing condom use, decreasing HIV risk, and increasing PrEP awareness, uptake, adherence, and retention. The limited number of interventions in the PrEP continu-um of care indicates a need for the uptake of dissemination and implementation science (D&I) frameworks. D&I could help facilitate the translation of evidence-based practices, interventions, and policies to address the HIV crisis in Latin America.